What did we learn after the 2020 pandemic? Seroprevalence of SARS-CoV-2 infection in a North region of Portugal during 3rd lockdown - Carvalho, Paula M.; Soares, Sandra C.; Castro, Ana R. (International Journal of Research in Medical Sciences, 2021)
Background: Serological studies of antibody prevalence in response to infection with the acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are useful to monitor the epidemic progression of the disease and to evaluate infection rates. In this study, we estimated the prevalence of anti-SARS-CoV-2 antibodies (IgM and IgG) in a Portuguese sub-district, during National lockdown - January-March 2021. Methods: In the seroepidemiological survey participants were tested for SARS-CoV-2 antibodies (IgM and IgG), in blood samples. The estimated seroprevalence and results were stratified by age, gender, education, occupational exposure, symptoms and previous SARS-CoV-2 infection. Results: Seroprevalence was 41.3%, (15.7% IgG positive, 11.6% IgM positive and 14% positive for both). The majority (74%) of the participants were working presentially and did the serological assay because they had either symptoms / positive contact (90%) or had a previous positive antigen test (36%). From all the seropositive cases only 44% were symptomatic. Our results show that seroprevalence of SARS -CoV-2 is high in the North, in parallel with the National Surveillance System. Seroprevalence was higher in woman than man and in adults older than 21. Almost all the people with symptoms or a positive contact had a positive test and were working at their regular places of work reflecting the danger of occupational exposure. Conclusions: These results suggest that, between January and March 2021, the restriction conditions were effective but unable to stop SARS-CoV-2 epidemic. It is essential to assess SARS-CoV-2 seroprevalence to monitor population immunity and if it lasts, specially from new COVID 19 variants.